Sustainable Development Goals as a normative framework for anti-poverty actions and environmental vulnerability (Research, Society and Development, 2025)
This study is based on the authors' concerns about multidimensional poverty. Amartya Sen advocates five types of freedom so that development can be achieved and, consequently, the forces of deprivation can be eradicated. The aim of this article is to make the case that, in addition to the five types of freedom advocated by Amartya Sen, governments and non-governmental institutions have a fundamental role to play in planning and implementing public policies aimed at sustainable development in rural and urban areas. The study was carried out between the years 2022 and 2024 and uses descriptive documentary and bibliographical research as its materials and methods. As a result, it seeks to align the conceptualization of public policies with the normative frameworks of the Sustainable Development Goals (SDGs), expanding the possibility of effective action by integrating economic, social and environmental dimensions in tackling the causes of poverty. Environmental sustainability, in turn, plays a crucial role, since the poorest are the most affected by changes in ecosystems, which reinforces the interdependence between human well-being and sustainability.